AC‐Driven Ultraviolet‐C Electroluminescence from an All‐Solution‐Processed CaSiO3:Pr3+ Thin Film Based on a Metal‐Oxide‐Semiconductor Structure. Issue 15 (8th April 2022) - Afandi, Mohammad M.; Kang, Hyeonwoo; Kang, Taewook; Park, Jehong; Kim, Jongsu
Abstract: An ultraviolet (UV) light source is continuously required for applications of sterilization as well as industrial value. In particular, research on materials and devices emitting UV‐C radiation in the range from 210 to 280 nm is very meaningful and challenging work. Herein, UV‐C electroluminescence (EL) from an all‐solution processed CaSiO3 :Pr 3+ (CSO) thin film is reported for the first time. The CSO thin film is formed on a Si substrate (size of 13 × 13 mm 2 ), and structurally, the UV‐C EL device has a metal‐oxide‐semiconductor (MOS) shape consisting of CSO and interlayered SiO x of 100 and 150 nm thickness, respectively, on Si. The emission and electrical properties of the UV‐C EL device are investigated under an alternating current system. The results reveal UV‐C emission peaking at 276 nm attributed to the 4f5d‐ 3 H(F)j transition of Pr 3+ ions within CSO, with a maximum output optical power of 8.37 µW cm −2 (power efficiency of 0.15%) at an operating voltage of 40 Vop (50 Hz). The work can provide a feasible method for realizing large‐area UV‐C‐emitting devices based on the MOS structure. Abstract : The ultraviolet (UV)‐C emitting device is introduced based on metal‐oxide‐semiconductor structure consisting of CaSiO3 :Pr 3+ and interlayered SiO x on Si. The results reveal UV‐C emission peaking at 276 nm attributed to electronic transition of Pr 3+ ions within CaSiO3, with a maximum output optical power of 8.37 µW cm −1 at an operation voltage of 40 V (50 Hz).